Formulasi Body Scrub Dengan Penambahan Charcoal Berbahan Dasar TKKS dan Limbah Padat Bromelin Sebagai Exfolian Agent - Windiastuti, Elsa; Nurbaiti, Nurbaiti; Afifah, Amalia; Laksono, Untung Trimo (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Body scrubs are skincare products specifically designed to help remove dead skin cells, while providing moisture to the skin. The main components in body scrubs often include exfoliating grains such as sugar, salt, seeds, or other natural abrasives, one of the promising natural ingredients to be used in the manufacture of body scrubs is biochar produced from empty fruit bunches (EFB) and bromelain solid waste. The purpose of this study was to determine the best ingredient formulation and to determine the potential and characteristics of EFB and bromelain waste when used as a body scrub. There were 3 treatments of adding EFB biochar (5g, 10g, 15g) and 3 treatments of adding bromelain solid waste (5g, 10g, 15g). The resulting data were presented descriptively. The results showed that the body scrub formulation with the addition of 10gr of EFB biochar was the formulation with the best characteristics, namely adhesion of 24.06 seconds, spreadability of 4.3 cm, pH 6.5, moisture content of 66.5%.